O CUSTO DA QUALIDADE APLICADO COMO FERRAMENTA DE GESTÃO PARA EMPRESAS DA CONSTRUÇÃO CIVIL - Thomaz, Mariana Campos Bravo; Nicoletti Jr, Alaércio; Fontanini, Patricia Stella Pucharelli (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The cost of quality is a concept used to demonstrate to the Company's management that programs to reduce failures and defects that cause customer dissatisfaction can be executed by generating returns on the initial investment. Quality does not cost and should be seen as an investment with assuring return to the company. What costs the company, and can be cause of significant losses, is the quality, that is, the lack of an acceptable level of quality in the market where we operate. In order, not to risk the idea that quality brings the company an additional cost, and that it might be unnecessary. The objective of this article is to present a model for calculating the cost of quality for real estate development companies (residential), so that it can be a management tool for strategic decision making to the management system of the organization. This model was configured to the reality of a real estate construction company XYZ, established in the State of São Paulo, considering as sampling for the application of model 04 (four) real estate projects in progress and the costs of the quality management system-maintained Headquarters.